Hyperbolic polariton-coupled emission optical microscopy - Li Shilong; Liu Zhaowei; Lee Yeon Ui (Nanophotonics)
A new type of optical microscopy based on hyperbolic polariton-coupled emission (HPCE) is demonstrated. By employing hyperbolic metamaterials as the substrate, we show a nearly 6-fold increase in fluorescence intensity in the HPCE microscope compared to total internal reflection fluorescence (TIRF) on glass substrates. Moreover, we achieve precise, time-dependent control of the fluorescence intensity by modulating the incidence angle with a galvo scanner. This tunability offers extensive potential for applications in super-resolution fluorescence microscopy and high-sensitivity sensing, enabling real-time fluorescence intensity adjustment.